Development of chromosome-specific BAC resources for genomics of bread wheat - Safár, J; Simková, H; Kubaláková, M; Cíhalíková, J; Suchánková, P; Bartos, J; Dolezel, J (Cytogenetic and genome research, 2010)
The large bread wheat genome (1C approximately 17 Gbp) contains a preponderance of repetitive DNA and the species is polyploid. These characteristics together serve to hamper the molecular analysis of the wheat genome. Its complexity can, however, be reduced by using flow cytometry to isolate individual chromosomes, and these can be exploited to construct chromosome-specific BAC libraries. Such libraries simplify the task of physical map construction, positional cloning and the targeted development of genetic markers. Rapid improvements in the efficiency and cost of DNA sequencing provide an opportunity to contemplate sequencing the wheat genome by preparing sequence-ready physical maps for each chromosome or chromosome arm in turn. The quality of the chromosome-specific libraries depends on their chromosome coverage and the mean insert size. First-generation libraries suffered from a relatively low mean insert size, but improvements to the protocol have generated a second wave of libraries with a significantly increased mean insert size and better chromosome coverage. Each chromosome (arm)-specific library is composed of a manageable number of clones, and so represents a practical tool in the area of wheat genomics.
Keywords: DNA, Plant; Chromosomes, Plant; Physical Chromosome Mapping; In Situ Hybridization, Fluorescence; genetické markery; genomika; pšenice; Genome, Plant; Flow Cytometry; hybridizace in situ fluorescenční; Genetic Markers; DNA rostlinná; Triticum; průtoková cytometrie; Chromosomes, Artificial, Bacterial; chromozomy rostlin; polyploidie; Genomics; Polyploidy; genom rostlinný; umělé bakteriální chromozomy; fyzikální mapování chromozomů; genová knihovna; Gene Library